The Dutch multicenter experience of the Endo-Sponge treatment for anastomotic leakage after colorectal surgery - van Koperen, P. J. (Springer-Verlag, 2008)
BACKGROUND: Anastomotic leakage is a feared complication following colorectal surgery and is associated with early and long-term morbidity and mortality. The presacral cavity as the result of leakage can be treated with an endo-sponge (B-Braun Medical). The aim of this study was to assess the effectiveness of endo-sponge treatment of the presacral cavity as the result of anastomotic leakage in the Netherlands. METHODS: Between July 2006 and April 2008, 16 patients (M/F = 9:7) with median age 64 years (range 19–78 years) who underwent surgery for rectal cancer (n = 13) or ulcerative colitis (n = 3) were treated with the endo-sponge treatment after anastomotic leakage. RESULTS: Of the 16 patients, eight patients started with the endo-sponge treatment within 6 weeks after the initial surgery. In these patients the endo-sponge was placed after a median of 24 days (range 13–39 days) following surgery. In the remaining eight patients the endo-sponge treatment was started later than 6 weeks after the initial surgery. In this group there was a median of 74 days (range 43–1,602 days) between surgery and the start of endo-sponge placement. There was closure in six out of eight patients (75%) in the group that started with the endo-sponge treatment within 6 weeks of surgery compared with three out of eight patients (38%) in the group that started later (p = 0.315). Closure was achieved in a median of 40 (range 28–90) days with a median number of 13 sponge replacements (range 8–17). CONCLUSIONS: Endo-sponge placement can be helpful in the treatment for anastomotic leakage after colorectal surgery and might prevent a chronic presacral sinus. However, it is not yet clear if this new treatment modality results in quicker healing.